Is COVID-19 a high risk factor for lung cancer?: A protocol for systematic review and meta-analysis. Issue 1 (8th January 2021) - Wu, Mingxin; Mou, Ruiyu; Liu, Xiaodi; Guo, Shanqi; Kong, Fanming; Li, Xiaojiang; Jia, Yingjie
Abstract: Introduction: COVID-19 has become a common threat to global human health and is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Some asymptomatic patients with early-stage lung cancer who have COVID-19 receive surgical treatment but develop severe pneumonia and other complications or even experience postoperative death, and they may have a worse prognosis compared with healthy individuals infected with COVID-19. However, there is no evidence that COVID-19 is a risk factor for lung cancer patients. This systematic review aims to evaluate the incidence and prognosis of COVID-19 in lung cancer patients and provide evidence-based medical support for clinical treatment. Methods: We will search 6 medical databases to identify eligible studies published from the establishment of the database to the present. The quality of the included literature will be evaluated using the bias risk assessment tool in Cochrane 5.1.0, and a meta-analysis will be performed using Stata 14.0. Heterogeneity will be statistically assessed using χ 2 tests. Results: The study will integrate existing research findings to investigate the prevalence and severity rate of patients with lung cancer infected with SARS-CoV-2 and analyze the prognosis and adverse clinical outcomes in patients with or without COVID-19. Conclusion: The results of this study provide evidence to support whether COVID-19 is a risk factor for lung cancer and provide guidance for clinical prevention and treatment based on the evidence obtained in light of the unpredictable threat posed by COVID-19. Ethics and dissemination: Ethics approval is not required for this systematic review as it will involve the collection and analysis of secondary data. The results of the review will be reported in international peer-reviewed journals. PRORPERO registration number: CRD42020195967.